A Study on Malaysian Crude Palm Oil Price Volatility - Mohamad Azwan Md Isa; Azlan Taha Baharim; Suhana Mohamed; Mohd Khairul Ariff Noh; Ferri Nasrul; Wan Muhd Faez Wan Ibrahim; Siti Salwa Hassan (Modern Perspectives in Economics, Business and Management Vol. 6, 2021)
One of the commodities that contributes to the Malaysian economy is the palm oil. Despite palm oil industry remarkable growth, the price of crude palm oil (CPO), namely the processed palm oil, has been highly volatile over the last 20 years. Hence, this paper aims to study the relationship and impacts of four macroeconomic determinants on Malaysian CPO prices; the exchange rate (EXC), inflation rate (INF), money supply (M3), and growth domestic product (GDP) covering a 20-year period from 1999 to 2018. From the study, we wish to reveal the determinants that have significant relationship with the CPO prices. In additition, we try to identify the determinants that have significant impacts on the CPO prices, either positively or negatively. The secondary annual time series data from the World Bank and DataStream is used in this study. Based on the results, the correlation test shows EXC has a negative correlation with CPO price, whereas INF, M3, and GDP have a positive correlation respectively. The multiple regressions tests reveal EXC and M3 are not significant determinants for the CPO prices whilst INF and GDP are significant. These findings could assist policymakers, palm oil industry players and manufacturers of CPO-based products to forecast and make the best policy, business, and investment decisions.